1994
DOI: 10.1161/01.res.75.2.296
|View full text |Cite
|
Sign up to set email alerts
|

Diminished transient outward currents in rat hypertrophied ventricular myocytes.

Abstract: Action potential duration is prolonged in ventricular hypertrophy induced by sustained pressure overload. Since the transient outward current (I(to)) is a major factor for determining action potential duration in rat ventricular cells, we used patch-clamp techniques to compare the characteristics of I(to) in normal and hypertrophied left ventricular cells of the rat. Left ventricular pressure overload was induced by partial ligation of the abdominal aorta for 4 to 6 weeks before study. Age-matched normal rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
41
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 40 publications
5
41
1
Order By: Relevance
“…A large fraction of the increase in APD has been attributed to a decrease in the Ca 2+ -independent transient outward potassium current (I to ) [1]. I to , however, is not uniformly distributed among the left ventricle.…”
Section: Introductionmentioning
confidence: 99%
“…A large fraction of the increase in APD has been attributed to a decrease in the Ca 2+ -independent transient outward potassium current (I to ) [1]. I to , however, is not uniformly distributed among the left ventricle.…”
Section: Introductionmentioning
confidence: 99%
“…Increased ␣ 1 -adrenergic receptor stimulation is also thought to contribute to the higher prevalence of arrhythmias (39). One of the consistent features of heart disease, in both human and experimental model systems, is prolongation of action potential duration (APD), which increases the propensity to develop cardiac arrhythmias (4,24,46). Thus it is possible that increased ␣ 1 -adrenergic stimulation would lead to delayed repolarization, which could increase electrical instability and contribute to arrhythmias in heart failure patients.…”
mentioning
confidence: 99%
“…It has been shown that long-term administration of IGF-I regulates the expression of the K ϩ channel in cultured neonatal rat ventricular myocytes (18). Most studies regarding the electrophysiological alterations associated with cardiac hypertrophy were performed on the pressure-overload model, which has been associated with reduction in I to (6,15,16,53) and no change (6,57) or a decrease in I K (13,14,29,30) and I K1 (5,15,37). Interestingly, Brooksby et al (5) have shown that the electrical remodeling related to cardiac hypertrophy was restricted to a decrease in I K1 current density with no difference in the resting potential level of cardiomyocytes from control and spontaneously hypertensive rats.…”
mentioning
confidence: 99%